Development of Service Culture as a Strategy to Strengthen Collaborative and Integrity-Based Work Culture Among the Academic Community at ITKES Wiyata Husada Samarinda - Agung Solihin; Achmad Tarmizi (Abdimas Paspama, 2026)
This community service program aims to develop a service culture as a strategic approach to strengthening collaborative and integrity-based work culture among the academic community at ITKES Wiyata Husada Samarinda. Preliminary analysis indicated that although standard operating procedures and formal codes of ethics were already in place, the practical implementation of service-oriented values, inter-unit collaboration, and professional integrity in daily academic and administrative services had not been fully optimized. The program was implemented using a participatory approach through structured training, interactive workshops, collaborative simulations, and integrity-focused mentoring. Program outcomes were evaluated using pre- and post-assessments of participants’ understanding and feedback on perceived changes in service practices. The results show improvements in participants’ awareness of service culture principles, strengthened collaborative practices across units, and enhanced ethical sensitivity in service delivery. These findings indicate that PKM-based interventions can function as an effective instrument for internal capacity building and organizational culture development in higher education institutions